Effect of Citizenship Rights Education on Social Resilience and Career Interest in Students of Abadan Islamic Azad University - Forough Mardani; Abbas Gholtash (Iranian Journal of Educational Research)
Objective: The aim of the present study was to determine the effect of citizenship rights education on social resilience and career interest of students of Abadan Islamic Azad University. Methods: In terms of its applied purpose, this study was a semi-experimental study with a pre-test and post-test with a control group in terms of field data collection. The statistical population of the study consisted of all students of Abadan Islamic Azad University in 2024, from which 30 people (15 people for each of the experimental and control groups) were selected by purposive sampling method and were randomly assigned to the experimental and control groups. In order to collect data, Connor and Davidson's Resilience Questionnaire and Holland's Career Interest Questionnaire were used. The data were analyzed using multivariate analysis of covariance. Results: The results showed that citizenship rights education was effective on social resilience and career interest in students (P<0.01). Conclusions: The results obtained can be utilized in formulating interventions that effectively enhance students' career interest and psychological resilience.